Development of amino acid balanced food systems based on wheat flour and oilseed meal - Papchenko, Victoriia; Matveeva, Tatiana; Bochkarev, Sergiy; Belinska, Anna; Kunitsia, E.; Chernukha, Anton; Bezuglov, Oleg; Bogatov, Oleg; Polkovnychenko, Dmytro; Shcherbak, Sergey (PC тесhnology сеntеr, 2020)
The analysis of the main methods of increasing the nutritional and biological value of wheat flour has been conducted. Considerable attention is paid to the issue of adjusting the protein content in flour due to additives. The relevance of improving the amino acid composition of flour protein is emphasized. The feasibility of comprehensive studies for the development of food system formulations with a balanced amino acid composition based on wheat flour and oilseed meal is substantiated. The amino acid content has been experimentally determined and the biological value of raw materials proteins for food systems which are sunflower and soybean meal has been calculated. The mixture composition of sunflower and soybean meal with an improved amino acid composition has been scientifically substantiated. It has been found that the protein composition of the meal mixture is maximally close to the reference in terms of the content of leucine, lysine and the amount of sulfur-containing amino acids (methionine, cystine). The score of isoleucine, tryptophan, phenylalanine and tyrosine in the protein composition of oilseed meal is 1.1–1.47 times higher than the reference. The amino acid composition has been calculated and the biological value of the protein of food systems containing 80–90 % wheat flour and 10–20 % composition of soybean and sunflower meal with improved amino acid composition has been determined. It has been found that the formulation of the food system containing 20 % of the composition of meal mixture and 80 % of wheat flour has the greatest biological value in comparison with wheat flour. In this food system, the limited amino acids – lysine and sulfur-containing (methionine and cystine) are the closest to the reference one and are 67.68 % and 70.12 %. The fatty acid composition has been experimentally determined. The biological effectiveness of the fats of the developed food systems has been calculated. The closest to the fatty acid ratio recommended by nutritionists is the food system with a ratio of meal mixture: wheat flour of 20:80. The resulting formulations of food systems will be useful in technologies of flour products with high biological value.
Keywords: wheat flour; sunflower meal; soybean meal; essential amino acids; amino acid score; fatty acids; food systems